Comparative Evaluation of Effectiveness of IAVchip DNA Microarray in Influenza A Diagnosis - K. T. Sultankulova; O. V. Chervyakova; N. S. Kozhabergenov; K. A. Shorayeva; V. M. Strochkov; M. B. Orynbayev; N. T. Sandybayev; A. R. Sansyzbay; A. V. Vasin (The Scientific World Journal)
The paper describes comparative evaluation of IAVchip DNA microarray, reverse transcription PCR (RT-PCR), and real-time RT-PCR versus virus isolation in chicken embryos and shows their diagnostic effectiveness in detection and subtyping of influenza A virus. The tests were evaluated with use of 185 specimens from humans, animals, and birds. IAVchip DNA microarray demonstrates higher diagnostic effectiveness (99.45%) in early influenza A diagnosis as compared to the real-time PCR (98.38%) and RT-PCR (96.22%), thus showing its clear superiority. Diagnostic sensitivity of IAVchip DNA microarray (100%) exceeds the same of RT-PCR (95.95%) and real-time RT-PCR (97.96%) in the range of estimated confidence intervals. IAVchip DNA microarray and real-time RT-PCR displayed equal diagnostic specificity (98.85%), while diagnostic specificity of RT-PCR was 96.40%. IAVchip DNA microarray has an advantage over the other tests for influenza A diagnosis and virus identification as a more rapid method that allows performing simultaneous detection and subtyping of about tens of specimens within one experiment during 8–10 hours. The developed IAVchip DNA microarray is a general test tool that enables identifying simultaneously 16 hemagglutinin (HA) and 9 neuraminidase (NA) subtypes of influenza A virus and also to screen the influenza A viruses from humans, animals, and birds by M and NP genes.